The Impact of Council's Internal Decision-Making Rules on the Future EU - Mika Widgrén (Aboa Centre for Economics (ACE), 2008)
This paper deals with the voting rules in the EU Council. Both internal and external impact of the voting rules are evaluated. Internal impact affects the distribution of power among the member states and external impact affects power relations between the main decision-making bodies in the EU. One of the main lessons of the analysis is clearly to explain why the design of Council voting rules has required so much bargaining and cumbersome marathon negotiations.
Keywords: C70; D71; H77; 330; European integration; Council of Ministers; power